Socio-economic factors affecting the academic performance of private university students in Bangladesh: a cross-sectional bivariate and multivariate analysis - Rahman, Sumaia; Munam, Al Muktadir; Hossain, Ahammad; Hossain, A. S. M. Delwar; Bhuiya, Rejvi Ahmed (SN Social Sciences, 2023)
Education is considered the most significant factor in producing human resource developments in terms of social, cultural, technological, economic, and overall national perspectives. Higher education is influenced by several factors that affect the quality of students’ education and outcomes. Most students in Bangladesh study at private universities from various socioeconomic conditions. Some of the factors have restricted their ability to attain higher education and as a result, impacted their academic performance. The goal of this study was to explore those socioeconomic factors affecting the academic performance of private university students in Bangladesh. The primary dataset was collected through an online survey from three private universities in Bangladesh named Varendra University (VU), Daffodil International University (DIU), and City University (CU). The Chi-square tests indicate that the age, gender, studying on a subject of their own choice, getting the right direction to make studying comfortable, consulting with the teacher about learning, family status, etc. variables significantly impacted their cumulative grade point average (CGPA). Relationships with parents and the opportunity to share opinions with parents were also significantly associated with their results. According to the multinomial logistic regression model age, gender, employment status, choice of own study field, getting the right direction, previous academic result, consultation with teachers, father's annual income, family status, and relationship with parents are found to be statistically significant determinants of academic performance. Considering the reality and outcomes of this study, to improve academic performance, parental involvement needs to be increased, and they must provide financial and material support to their offspring for their academic success. Moreover, for achieving a satisfactory CGPA, the students need to build friendly relationships with their parents and have regular consultations with their teachers as well.